Pelatihan Kompetensi Guru dalam Menggunakan QR Code Berbasis Android untuk Presensi Siswa pada SMA Negeri 1 Latambaga, Kolaka - Yodang Yodang; Akhmad Fadli Ibrahim; Nuridah Nuridah (Institut Agama Islam Negeri Bengkulu, 2020)
The community engagement program aims to 1). Introduce informationtechnology for educational purposes, 2). Train teachers in order to apply QR Codeapplication for students’ attendance through online with android based, 3) Teacherswill able to apply for students’ attendance checklist through online. The communityengagement program structured conducted which began with a survey and initialassessment as a first step, and followed by delivering program, and monitoring andevaluation steps. The program conducted based on goals and achievement criteria.This community engagement held in the beginning of the semester on 22th Febryuary2020 at SMA Negeri 1 Latambaga, Kolaka regency, Sulawesi Tenggara. There are 25teachers evolved in this program. The results of this program were improvement ofteachers’s knowledge on information technology for educational purposes,understanding of teachers to used QR code for online students presence record, andable to apply QR code for QR code as online students presence record with androidbased.